2006
DOI: 10.1074/jbc.m601457200
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Dependence to HIV-1 Entry Inhibition

Abstract: HIV-12 cellular invasion proceeds through fusion of viral and cellular membranes, a process mediated by the viral surface glycoprotein Env in response to binding cellular receptors (1, 2). Functional Env is composed of two noncovalently linked subunits, gp120 and gp41, arranged as a trimer of heterodimers on the virion surface. The interaction of gp120 with cellular CD4 and a chemokine receptor promotes structural rearrangements that ultimately lead gp41 to insert its N-terminal fusion peptide segment into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
112
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(125 citation statements)
references
References 41 publications
11
112
1
1
Order By: Relevance
“…More fundamentally, it remains to be seen whether a robust antibody response targeting the transient and sterically occluded prehairpin intermediate can be elicited. Recent studies suggest that access to this region during the viral fusion process may be limited by steric hindrance, which would be a significant barrier to the development of an effective vaccine (39,40). Our observation that neutralization potency and the quantity of D5-like antibodies are lower in rabbits than in guinea pigs may point to increased difficulty in eliciting protective neutralizing antibody titers in higher species, including primates.…”
Section: Discussionmentioning
confidence: 49%
“…More fundamentally, it remains to be seen whether a robust antibody response targeting the transient and sterically occluded prehairpin intermediate can be elicited. Recent studies suggest that access to this region during the viral fusion process may be limited by steric hindrance, which would be a significant barrier to the development of an effective vaccine (39,40). Our observation that neutralization potency and the quantity of D5-like antibodies are lower in rabbits than in guinea pigs may point to increased difficulty in eliciting protective neutralizing antibody titers in higher species, including primates.…”
Section: Discussionmentioning
confidence: 49%
“…The trimer's binding to the pocket was too tight (low to mid pM) to measure accurately by SPR (the value reported in Table 1 is approximate and likely underestimates the trimer's true affinity). Interestingly, the trimer's potency against HXB2 did not improve as much as expected from its K D , suggesting that trimer potency against HXB2 may have reached a potency limit imposed by association kinetics, as has been reported for another entry inhibitor, 5-helix (34). This kinetic limitation is expected because the exposed N-trimer has an Ϸ10-to 20-min lifetime in the gp41 prehairpin intermediate (4)(5)(6), similar to the time required for binding of our peptides at mid to high pM concentrations.…”
Section: Resultsmentioning
confidence: 72%
“…the HR1/HR2 bundle (8,16) although more recent results have demonstrated that this relationship may be complex (32,33). Using circular dichroism, the stability of the engineered HR2 peptides was determined in complex with the 51-aa HR1 target, T-865 (13).…”
Section: Resultsmentioning
confidence: 99%